Risk Assessment of Technology Development in Petroleum Industry Equipment (Drill Bits) - Mohammad Naghizadeh; Saeed Pak Seresht; Batul Ebrahimi (بهبود مدیریت, 2016)
Localization of advanced petroleum industry technologies has been one of the key priorities of Iranian policymakers. According to the high cost of technology development in this industry, identification of technology development risks is crucial for the policymakers and technology developers. The main objective of this article is identification and assessment of the technology development risks in petroleum industry equipment focusing on Drill Bits. To address this objective, after literature review and exploratory interviews with experts, 38 risks were identified and classified into five dimensions including institutional, technological, market, financial and operational ones. FMEA method was used to assess these risks. Accordingly, their severity, likelihood of occurrence and detection were assessed. Five risks were selected as the risks with higher RPN. Providing expensive bank guarantees, testing the products in the real fields, and changes of macro economy indicators are the most important risks respectively. Facilitating the process of bank guarantee providing for these firms and developing the real test fields are some of the most important suggestions to the policy makers. As well, providing the minimum necessary demands before entering the localization process and being accurate in partner selection according to its specialty, aims and the related background are some of the most important suggestions to these firms’ managers.